Know Risk - United Nations (Geneva, Zwitzerland : United Nations, 2005)
The international strategy for disaster reduction alms at building disaster resilient communities by promoting increased awareness of the importance of disaster reduction as an integral component of sustainable development, eith the goal of reducing human, social, economic and environmental losses due to natural hazards and related technological and environmental disasters.
Contenido I. The World of Risk II. Governance & Institutional Policy III. Risk Identification & Assessment IV. Information, Knowledge & Experience V. Reducing Disaster Risks
Incluye índice general
Incluye bibliografía
Keywords: ADMINISTRACIÓN DE RIESGOS; EFECTOS DE DESASTRES NATURALES; DESASTRES NATURALES